Hubungan Asupan Karbohidrat, Asupan Lemak Dan Indeks Massa Tubuh Dengan Tingkat Kebugaran Mahasiswa di Unit Kegiatan Mahasiswa Sepakbola Universitas Negeri Yogyakarta - Rhomadani, Anggita Sari Nur, Siti Zulaekah, A., M.Si, Wahyuni, SSt.FT.M.Kes (2015)
Correlations Between Carbohydrate Consumption, Fat Consumption and Body Mass Index With Fitness Level of Student at The Unit of Students Soccer Activities of Yogyakarta State University Background: College student constitutes fraught term problem and emotional stress. One of factor which regard fitness is nutrient intake (carbohydrate and fat) and nutrient state (body mass Index). Football is athletics claiming fitness of optimal body. Objective: To analyzed correlations between carbohydrate consumption, fat consumption and body mass index with fitness level of student at Soccer Student Activity Units Univercity Yogyakarta Research methods: This research was observational with cross sectional draft research. The carbohydrate and fat consumption data collected by form food recall 4x24 hours with not successively, body mass index data collected by anthropometry measurement and fitness level measured with bleep test methods. 36 research subject taken by simple random sampling. Pearson product moment correlation test to analyzed the correlations carbohydrate consumption, fat consumption and body mass index with fitness level. Result: Most research subject (41,7%) had fitness level enough. Carbohydrate consumption of research subject equal to 30,6% normal and fat consumption equal to 75% experiencing of heavy deficiencies. Body mass index of research subject 94,4% having normal nutritional status. Conclusion: There was correlation between carbohydrate consumption (p=0,039, r=0,346) and body mass index (p=0,002, r=-0,492) with fitness level of Student at The Unit of Students Soccer Activities of Yogyakarta State University. There was no correlation between fat consumption with fitness level of Student at The Unit of Students Soccer Activities of Yogyakarta State University (p=0,457). The Unit of Students Soccer Activities of Yogyakarta State University require to give education to its members, about nutrition consumption for athlete to getting optimal fitness and can reach wanted achievement.